THE MONITORING OF MANGROVE VEGETATION COMMUNITY STRUCTURE IN SEGARA ANAKAN CILACAP FOR THE PERIOD OF 2009 AND 2015 - Steni Dwiyanti Koswara; Erwin Riyanto Ardli; Edy Yani (Scripta Biologica, 2017)
Over-exploitation and land-use conversion into aquaculture ponds have damaged the mangrove ecosystem. The extreme environment condition resulting in sedimentation led to the reduction of lagoon area and eventually of mangrove vegetation community. It was, therefore, necessary to conduct sustainable mangrove management through the monitoring system. Changes in the mangrove community were monitored periodically by evaluating width changes and land cover distribution. This study aimed to monitor the structure of mangrove community and changes occurring for the period of 2009 and 2015 by applying the purposive sampling method. The samples were mangrove vegetation community at several different locations. The samples were taken from nine stations with three replicates. There were 14 species of mangrove from six families. Mangrove trees were mostly found in the western area, while mangrove sapling and seedling mostly found in the east. Most of the stations showed a moderate level of diversity index and good productivity except station four. Mangrove forest in Segara Anakan had significant changes from 2009 up to 2015 due to the reduction of mangrove diversity.